Flipped classroom to improve students’ understanding in a research methodology class in a public higher education institution - DeWitt, Dorothy; Alias, Norlidah; Siraj, Saedah (2014)
As novice researchers, postgraduate students in a Masters in education program are required to take a research methodology course in which the characteristics, design, and methodologies of different types of research are examined. There is a tremendous amount of information and a large amount of readings to be done, and most students finding difficulty in understanding the different research methods well. In this study, an exploratory implementation study is done to determine if a Flipped Classroom model could be implemented in a research methodology class to address this issue and to increase quantity and quality of interactions for improving learning. The study employs a design and developmental approach to investigate the possibility of implementing this design among 10 volunteers. Data from interviews, observation, as well as pre and post tests were collected to determine if this model could be implemented on a larger scale. This is a preliminary study and the findings cannot be generalized. However, this research may still provide insights on the implementation of Flipped classroom, and enable researchers to determine the possibilities for it to be extended to other subjects.